2014
DOI: 10.1371/journal.pone.0086863
|View full text |Cite|
|
Sign up to set email alerts
|

"Timed Up & Go": A Screening Tool for Predicting 30-Day Morbidity in Onco-Geriatric Surgical Patients? A Multicenter Cohort Study

Abstract: ObjectiveTo determine the predictive value of the “Timed Up & Go” (TUG), a validated assessment tool, on a prospective cohort study and to compare these findings to the ASA classification, an instrument commonly used for quantifying patients’ physical status and anesthetic risk.BackgroundIn the onco-geriatric surgical population it is important to identify patients at increased risk of adverse post-operative outcome to minimize the risk of over- and under-treatment and improve outcome in this population.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
93
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 149 publications
(100 citation statements)
references
References 34 publications
(44 reference statements)
2
93
0
Order By: Relevance
“…CGA studies have demonstrated the predictive value of these ADL/IADL tests with regard to survival, postoperative morbidity and mortality, and chemotherapy toxicity [13]. As an alternative to time-consuming evaluations, some very simple measures have been developed to evaluate functional performance, such as the ''Timed Up & Go'', which appears to be valuable for predicting postoperative complications after oncologic surgery [16]. Shortened forms of CGA have been proposed, although they require validation in routine clinical settings [17].…”
mentioning
confidence: 99%
“…CGA studies have demonstrated the predictive value of these ADL/IADL tests with regard to survival, postoperative morbidity and mortality, and chemotherapy toxicity [13]. As an alternative to time-consuming evaluations, some very simple measures have been developed to evaluate functional performance, such as the ''Timed Up & Go'', which appears to be valuable for predicting postoperative complications after oncologic surgery [16]. Shortened forms of CGA have been proposed, although they require validation in routine clinical settings [17].…”
mentioning
confidence: 99%
“…The proportion of patients with low grip strength was higher than that seen in the Cardiovascular Health Study (20%) 28 , and average gait speed was slower than speeds measured for community-dwelling older adults in all but one study in a large systematic review 18 . Compared with other studies of older cancer patients, our study had a larger proportion of patients with low grip strength (50% vs. 21.4%) 32 and a higher proportion with a gait speed less than 1.0 m/s (91.7% vs. 54.4%) 32 , but a smaller proportion with a prolonged time on the tug test 7,[33][34][35][36][37][38] . Because gait speed was not reported in the latter studies, it is difficult to know whether average gait speed was slower in their patients than in ours.…”
Section: Discussionmentioning
confidence: 55%
“…• Geriatric oncologists must ensure that older patients who are to undergo extensive surgery or systemic treatment are screened for frailty with a risk-assessment frailty screening tool (Hamaker et al, 2012;Decoster et al, 2015;Huisman et al, 2014) and subsequent comprehensive geriatric assessment when indicated. Whenever possible an estimation of life expectancy (e.g.…”
Section: Essential Requirementsmentioning
confidence: 99%